Carbon black nanospheres modified with Cu (II)-phthalocyanine for electrochemical determination of Trimethoprim antibiotic - Guaraldo, Thais T.; Goulart, Lorena A.; Moraes, Fernando C.; Lanza, Marcos R.V. [UNESP] (Elsevier, 2019)
This work investigates the electrochemical sensing properties of glassy carbon (GC) electrodes modified with Printex L6 carbon black (PC) and copper (II) phthalocyanine (CuPh) films. Successful incorporation of the CuPh into carbon black was confirmed by FEG-SEM, EDS and TEM analysis. The transition from nanocrystalline graphite to amorphous carbon material could be evidenced for Printex L6 carbon black using Raman analysis. The modified material (CuPh/PC/GC) demonstrated electrocatalytic effect towards TMP detection according to cyclic voltammetric studies. CuPh modification resulted in strong adsorption to carbon black and TMP due to π-π interactions. Scan rate studies proved reactions across the electrode/electrolyte interface progressively change from adsorption to diffusion. The developed method presented linear relationship in the ranges of 0.4–1.1 µmol L −1 and 1.5–6.0 µmol L −1 with limit of detection of 0.6 µmol L −1 under optimized experimental conditions. The proposed CuPh/PC/GC electrode was effectively employed towards the detection of TMP in natural water samples.
Keywords: Carbon black; Copper phthalocyanine; Environmental samples; Printex L6; Trimethoprim determination